2006
DOI: 10.1037/1528-3542.6.2.163
|View full text |Cite
|
Sign up to set email alerts
|

Romantic love and sexual desire in close relationships.

Abstract: Drawing on recent claims in the study of relationships, attachment, and emotion, the authors hypothesized that romantic love serves a commitment-related function and sexual desire a reproduction-related function. Consistent with these claims, in Study 1, brief experiences of romantic love and sexual desire observed in a 3-min interaction between romantic partners were related to distinct feeling states, distinct nonverbal displays, and commitment- and reproductive-related relationship outcomes, respectively. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
192
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 233 publications
(199 citation statements)
references
References 145 publications
5
192
0
2
Order By: Relevance
“…Our studies add to the growing list of work investigating function-specific effects of emotion (Buss, Larsen, Westen, & Semmelroth et al, 1992;Fessler, Pillsworth, & Flamson, 2004;Gonzaga et al, 2001;Gonzaga et al, 2006;Lerner & Keltner, 2001). We supported the hypothesis that love, but not sexual desire, is a commitment device, helping an individual suppress thoughts of an attractive other.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Our studies add to the growing list of work investigating function-specific effects of emotion (Buss, Larsen, Westen, & Semmelroth et al, 1992;Fessler, Pillsworth, & Flamson, 2004;Gonzaga et al, 2001;Gonzaga et al, 2006;Lerner & Keltner, 2001). We supported the hypothesis that love, but not sexual desire, is a commitment device, helping an individual suppress thoughts of an attractive other.…”
Section: Discussionsupporting
confidence: 76%
“…Past research has shown that romantic partners are sensitive to the behavioral cues of love from their partner (Gonzaga et al, 2001(Gonzaga et al, , 2006. The current work is the first to show a causal link between the experience of love and cognitive processes that bolster commitment to a partner within an individual's own mind.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…In humans, intranasal administration of oxytocin increases generosity (8), trust (9), eye gaze (10), and the ability to infer the affective mental states of others (11). Furthermore, assessments of plasma oxytocin in humans find that oxytocin levels relate to parentchild bonding behaviors (12), feelings of romantic love and trust (13), and empathy and subsequent generosity toward strangers (14).…”
mentioning
confidence: 99%